A national survey of the management of patients with incidental meningioma in the United Kingdom. (4th July 2017) - Mohammad, Mujtaba H.; Chavredakis, Emmanuel; Zakaria, Rasheed; Brodbelt, Andrew; Jenkinson, Michael D.
Abstract: Background: Incidental meningiomas are increasingly being diagnosed due to widespread use of brain imaging. Treatment options include surveillance, surgery and stereotactic radiosurgery, but the natural history of these tumours is not fully understood and there are no accepted management guidelines to aid clinical decision-making. The aim of this study was to assess current practice in the United Kingdom and identify areas of variation for further study. Methods: A questionnaire was distributed to all members of the Society of British Neurosurgeons (SBNS). The main components of the survey included the assessment of which factors and tumour characteristics are considered in the management and follow-up of incidental meningiomas. Two case scenarios were also presented. Results: The response rate was 12.5% (44 completed surveys) with 74% (25/34) of neurosurgical centres represented. Absence of calcification was only considered by 36% (16/44) of neurosurgeons. Most neurosurgeons opt for surveillance at initial presentation, and the length of follow-up was 5 years (14/33) and 10 years (11/33). The case scenarios highlighted that tumour growth at follow-up resulted in a preference to change from surveillance to treatment with surgery or SRS. SRS was preferred in skull-base (23/36) and medial sphenoid wing (16/39) tumours. Conclusions: This survey has demonstrated that certain aspects of incidental meningioma management show variation and remain controversial. Further research through prospective cohort studies is required to provide evidence to support guidelines for the management of incidental meningiomas.